2021
DOI: 10.3390/cells10102783
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aldynoglia Cells in Neuroinflammatory and Neuroimmune Responses after Spinal Cord Injury

Abstract: Aldynoglia are growth-promoting cells with a morphology similar to radial glia and share properties and markers with astrocytes and Schwann cells. They are distributed in several locations throughout the adult central nervous system, where the cells of the aldynoglia interact and respond to the signals of the immune cells. After spinal cord injury (SCI), the functions of resident aldynoglia, identified as ependymocytes, tanycytes, and ependymal stem cells (EpSCs) of the spinal cord are crucial for the regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…The pro-inflammatory macrophage/microglia (M1 subsets) and anti-inflammatory macrophage/microglia (M2 subsets) are significant. Therefore, regulating the polarization of M1 and M2 macrophages/microglia can affect the inflammatory response process after SCI ( Buzoianu-Anguiano et al, 2021 ; Ding et al, 2021 ; Hashemizadeh et al, 2022 ). Previous studies have shown that acupuncture can ameliorate SCI by regulating M1 and M2 macrophages ( Zhao et al, 2017 ).…”
Section: Mechanism Of Acupuncture Therapy In Spinal Cord Injurymentioning
confidence: 99%
“…The pro-inflammatory macrophage/microglia (M1 subsets) and anti-inflammatory macrophage/microglia (M2 subsets) are significant. Therefore, regulating the polarization of M1 and M2 macrophages/microglia can affect the inflammatory response process after SCI ( Buzoianu-Anguiano et al, 2021 ; Ding et al, 2021 ; Hashemizadeh et al, 2022 ). Previous studies have shown that acupuncture can ameliorate SCI by regulating M1 and M2 macrophages ( Zhao et al, 2017 ).…”
Section: Mechanism Of Acupuncture Therapy In Spinal Cord Injurymentioning
confidence: 99%
“…The regenerative capacity of the adult mammalian spinal cord after injury is extremely limited, mainly due to multifaceted adverse factors in addition to inflammatory cell activation that together contribute to a non-permissive environment and minimal functional recovery ( 1 , 16 , 160 , 161 ). Neuroinflammation is part of the primary responses to injury and might be linked to the characteristics of innate immune cells and immunological molecules involved in the injury area ( 19 , 162 , 163 ).…”
Section: Immune Properties Of Oecsmentioning
confidence: 99%
“…Once OECs are implanted into the injured spinal cord zone, numerous molecules released from OECs, as acute positive and negative regulators participate in modulating the expression and activity of cytokines and chemokines ( 167 ). For instance, the anti-inflammatory cytokines IL-4, IL-10, TGF-β, and IL-13 produced by OECs protect against cell degeneration or death by modulating iNOS and NO production in the context of LPS/IFN-γ stimulation ( 90 , 158 , 159 , 161 ). Meanwhile, these anti-inflammatory cytokines are indicative of inhibition of the release of the pro-inflammatory cytokines TNF-α, IL-1β, IL-2, and IL-6 ( 161 , 165 ).…”
Section: Immune Properties Of Oecsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of structural and functional diversity within the glial population explains the diverse roles played by these cells in a region-specific manner. In their review, Buzoianu-Anguiano et al shed light on molecular and functional aspects of a group of glial cells, collectively named aldynoglia [ 8 ]. They further extended their discussion to the regenerative potential of aldynoglia in spinal cord injury and suggested many mechanisms by which these cells can be used as therapeutics in spinal cord injury.…”
mentioning
confidence: 99%